(untitled) - Hvizdakova, Zuzana (Doprava a spoje, 2012)
This article titled "Taxes and fees related to the motor vehicle operation in Sweden" describes taxes on motor vehicle and fees in Sweden and the way of these taxes and fees payment. First part of this article is focused on motor vehicle tax and system of its payment including tax amount and obligations of taxable person. The second part describes fees that must be paid by foreign motor vehicle operator who use motor vehicles over 12 tons in Sweden. In this part are also listed road segments that are charged and fee amount. Last part of the article is focused on congestion tax that was introduced in Stockholm and will be introduced in Gothenburg.